From paternalism to self-determination: examining evolving tribal-federal relationships and co-management arrangements through three case studies - Clarita Lefthand-Begay; Lauren Redmore; Christopher Armatas; Jesse Brisbois; Kunsang Choden; Dara Craig; Angelo Baca; Jaime Martin; Michael Ross; Regina Lopez-Whiteskunk; Alfred Lomahquahu; Monte Mills (Humanities & Social Sciences Communications)
Abstract As governments around the world seek to develop and implement co-management practices with Indigenous peoples and local communities, there are many questions about how to foster collaborative and just agreements that support self-determination. Despite policy advancements enabling more co-management and shared stewardship within the United States (U.S.), possibilities for co-management are complicated by historical injustices that have hindered Tribal access to ancestral land and cultural practices. We use a multiple case study approach, examining three case studies from the Western U.S. that illustrate challenges facing Tribes and interventions used to improve land management relationships. The first case study focuses on the relationship between the Oglala Sioux Tribe and the U.S. government and highlights that historical injustices continue to affect Tribal land management. The second case study explores the collaborative management of Bears Ears National Monument, showcasing a decolonized approach endorsed by Tribes seeking to reclaim their inherent rights to the land. The third case study examines the Snoqualmie Tribe as an example of a sovereign Tribe embodying the concept of “Land Back.” Tribes have utilized strategies, such as co-management, coalition building, and land reacquisition, to maintain control over lands important to their populations. These strategies promote power-sharing, resource distribution, trust-building, and the integration of Indigenous knowledge with Western science. Nonetheless, failure to recognize and account for the weight of broken treaties, discriminatory laws and policies, and the historical trauma caused by these injustices emphasizes the importance of understanding the dynamics surrounding Tribal land management. As government-led land management paradigms around the world shift to consider self-determination of Indigenous nations and communities as a critical piece of improved stewardship, decision makers have many historically-informed dynamics to consider when shaping future co-management practices. KEYWORDS: co-management, Indigenous, “Land Back”, stewardship, Tribes, and sovereignty.